Catalisador de Jacobsen e ferro-cyclam suportados em quitosana como modelos do CYP450 para oxidação de corantes têxteis - Rocha, Evelyn Monique Lima (2019)
Biotransformation of textile dyes resulting from reduction of azo dye binding or cytochrome P450 (CYP450) catalyzed oxidation has been studied due to the formation of byproducts with carcinogenic, mutagenic and genotoxic potential. Due to the difficulty of working with enzymes, the use of CYP450 model compounds has been highlighted. These catalysts have been used anchored to solid supports that prevent complex inactivation, increase catalytic activity and selectivity, and allow their reuse. Chitosan (QT) stands out among the other supports, because it is a biopolymer, a natural, renewable, biodegradable compound with affinity for metal ions. In this work, the Iron-Cyclam (FeCy) and Jacobsen's (JBN) catalysts were used as CYP450 models immobilized on chitosan and applied to the oxidation of reactive orange 16 (LD16), dispersed orange 3 (LD3) and methylene blue (AM) dyes. From the characterization of these supported materials, using Fourier Transform Infrared spectroscopy (FTIR) techniques, thermal analysis, and Scanning Electron Microscopy / Dispersive Energy Spectroscopy (SEM / EDS); Evidence could be obtained that catalysts are present in chitosan without significant changes in matrix structure. These materials were quantified using the FAAS technique, with values of 9.0x10-6 mol Jacobsen catalyst and 1.9x10-5 mol Fe-Cyclam per gram of chitosan. The dyes LR16 and LD3 were adsorbed by chitosan, making it impossible to study the action of catalysts. With the cationic dye, AM, it was possible to observe the oxidation of the dye and the influence of the pH in the reaction medium, presenting better results at pH 10 and 12. The highest percentage of oxidation was at pH 12 of 88% and 80% in the presence. the Jacobsen and Fe-Cyclam catalyst, respectively; revealing that the catalysts JBN-QT and FeCy-QT showed efficiency in AM oxidation.